Climate extremes, variability, and trade shape biogeographical patterns of alien species. Issue 4 (27th October 2020) - Liu, Xuan; Rohr, Jason R; Li, Xianping; Deng, Teng; Li, Wenhao; Li, Yiming
Abstract: Understanding how alien species assemble is crucial for predicting changes to community structure caused by biological invasions and for directing management strategies for alien species, but patterns and drivers of alien species assemblages remain poorly understood relative to native species. Climate has been suggested as a crucial filter of invasion-driven homogenization of biodiversity. However, it remains unclear which climatic factors drive the assemblage of alien species. Here, we compiled global data at both grid scale (2, 653 native and 2, 806 current grids with a resolution of 2°   ×   2°) and administrative scale (271 native and 297 current nations and sub-nations) on the distributions of 361 alien amphibians and reptiles (herpetofauna), the most threatened vertebrate group on the planet. We found that geographical distance, a proxy for natural dispersal barriers, was the dominant variable contributing to alien herpetofaunal assemblage in native ranges. In contrast, climatic factors explained more unique variation in alien herpetofaunal assemblage after than before invasions. This pattern was driven by extremely high temperatures and precipitation seasonality, 2 hallmarks of global climate change, and bilateral trade which can account for the alien assemblage after invasions. Our results indicated that human-assisted species introductions combined with climate change may accelerate the reorganization of global species distributions.